Telehealth—An Environmentally Friendly Way to Take Care of Patients with Inflammatory Bowel Disease - Srdjan Marković; Djordje Kralj; Tamara Knežević Ivanovski; Petar Svorcan (Medicina)
Background and Objectives: On 11 March 2020, our hospital adapted to the COVID-19 pandemic by becoming a temporary COVID-19 facility, leading to the suspension or delegation of non-COVID-19 services. Among the international IBD community, there were significant concerns regarding the neglect of immunocompromised IBD patients and their increased vulnerability to COVID-19. To address these challenges, the COVID-19 ECCO Taskforce recommended the implementation of telehealth. Following this recommendation, our hospital’s IT department integrated audiovisual hardware and software solutions to facilitate virtual consultations. This approach enabled patients and their local physicians to receive formal reports comparable to those issued during standard in-person care. Materials and Methods: We retrospectively analyzed data from patients diagnosed with Crohn’s disease and ulcerative colitis who participated in telemedicine consultations. Average distances and time saved were calculated using Google Maps, while carbon emissions and carbon footprint reductions were determined. Results: Between 11 August 2021 and 15 June 2023, 107 telehealth consultations were completed. Patients benefited from reduced travel distances, with an average saving of 168.28 km per consultation and a total reduction of 18,006 km. Travel time savings averaged 2 h and 22 min per consultation, amounting to a total of 252 h saved. The reduction in carbon emissions was calculated at 3.26 tons, equivalent to the annual absorption capacity of 109 fully grown trees, considering that an individual tree absorbs approximately 21.77 kg of CO2 annually. These findings underscore telemedicine’s role in reducing environmental impact while enhancing patient convenience. Conclusions: The adoption of telehealth successfully optimized outpatient clinic operations, maintaining high-quality patient outcomes while contributing to environmental sustainability.